RELATIONSHIP BETWEEN CIGARETTE SMOKE EXPOSURE WITH ASTHMA CONTROL LEVEL IN LUNG POLYCLINIC RSUD AISYIYAH PARIAMAN - ALPICES; DORA, MECHI SILVIA; RAHMIWATI (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2025)
Exposure to cigarette smoke contains various irritants and toxins that can damage the respiratory tract and trigger inflammatory reactions in the lungs. In children, exposure to cigarette smoke increases the likelihood of developing asthma early or worsening its symptoms. While in adults, continuous exposure to cigarette smoke can trigger asthma and worsen existing asthma conditions. The purpose of this study was to determine the relationship between exposure to cigarette smoke and the level of asthma control in asthma sufferers at the Lung Polyclinic of Aisyiyah Pariaman Hospital. This type of research is quantitative with a cross-sectional design approach. The study was conducted at the Lung Polyclinic of Aisyiyah Pariaman Hospital on July 15-17, 2024. The study population was asthma patients at the Lung Polyclinic of Aisyiyah Pariaman Hospital. The research sample was 40 asthma patients at the Lung Polyclinic of Aisyiyah Pariaman Hospital. Sampling was carried out using the accidental sampling technique with a sample size of 40 respondents. The data collection tool used a questionnaire. The data collected was primary data filled in by respondents in the questionnaire. Data analysis using Chi Square at the α level = 5%. The results showed that most respondents, namely 25 people (62.5%) were exposed to cigarette smoke. Most respondents, namely 25 people (62.5%) had uncontrolled asthma. Chi Square analysis showed p value = 0.00 <0.05. It can be concluded that there is a relationship between exposure to cigarette smoke and the level of asthma control at Aisyiyah Pariaman Hospital. The researcher's suggestion is that asthma sufferers should avoid triggers for asthma such as cigarette smoke wherever they are so that the level of asthma control can be optimized at home.